FAKTOR-FAKTOR KEBIASAAN SARAPAN PAGI DI SEKOLAH SMP NEGERI 09 BATU AJI KOTA BATAM TAHUN 2020 - Nathasha, Nathasha; Yunita, Prasida (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
School-age children (13-16 years) are an age group that begins to participate in various structured activities that require adequate intake of energy and nutrients every day. Without adequate daily intake of energy and nutrients, children will experience mental and physical fatigue, difficulty concentrating while studying and slow cognitive and behavioral development. Therefore, providing nutritious food for school-age children is very important, including the provision of breakfast. The aim of the researcher was to find out whether there was a relationship between knowledge and students' attitudes towards breakfast habits at SMP N 09 Batam City. This study used a cross sectional study carried out at SMP N 09 Batam City in August 2020. The population and research samples from 81 students were found to have a relationship between students' knowledge about nutrition and breakfast habits at SMP N 09 Batam City in 2020 with breakfast knowledge category. good on the availability of breakfast in the good category as many as 39 respondents (75.0%), obtained p value = 0.000 <0.05. The relationship between knowledge of attitudes towards breakfast habits with negative attitudes on the availability of breakfast in the good category was 30 respondents (63.8%), p value = 0.019 <0.05. The relationship between knowledge of breakfast and good knowledge on negative attitudes was 36 respondents (69.2%), p value = 0.000 <0.05. It can be concluded that Ho is rejected, meaning that there is a significant relationship between Knowledge and breakfast habits, attitudes with breakfast habits and knowledge with students' attitudes. It is hoped that as additional learning, students should know more about the importance of breakfast for the body to increase learning concentration and begin to realize the importance of breakfast in the morning and want to have breakfast, because remembering breakfast has many benefits